Literary Activities of the Students and Teachers of Kražiai College in the Seventeenth Century: Works Dedicated to the Samogitian Bishops - Nedzinskaitė, Živilė (Senoji Lietuvos literatūra, 2017)
Founded in 1616, Kražiai College became a cultural centre of Samogitia. Samogitian bishops and other distinguished people used to honour it with their visits. Led by their professor of rhetoric, students would welcome them with performances, recitations of panegyrics, and congratulatory orations. Some of these works were printed, others have survived in manuscripts, and still others are probably lost for good. There were about 36 of them in all. In the first paper of the planned cycle of articles, the author discusses occasional works created at Kražiai College in the seventeenth century, which were dedicated to the bishops of Samogitia. There were ten of them: eight works are extant, and two did not survive. The works dedicated to the Samogitian bishops point to several things. First of all, it is changes in the seventeenthcentury literary trends. At the beginning of the century, the leading position was taken up by panegyrics of various structures. Mostly they consisted of an armorial verse, an introductory speech in prose, a poem, and epigrammatic or emblematic appendices. Figures of a bishop’s coat of arms would almost without exceptions turn into the keystone of a panegyric: they were used to glorify a large diversity of virtues of the person congratulated. From the middle of the seventeenth century, the structure of the panegyrics began to change: it became much more varied and the common structural pattern was no longer adhered to. This was determined by a changing attitude towards the disciplines of poetics and rhetoric, new fashions in literature, and by the efforts of talented professors (Casimirus Koialowicz, Andreas Mlodzianowski). At the end of the century, congratulations to the bishops underwent a radical change: they mostly acquired the form of a performance written by the college’s teacher of rhetoric performed in honour of the distinguished addressee. Unfortunately, not a single text of a drama written in Kražiai in the seventeenth century has reached us. Information on the content of these dramatic works can be gathered from their descriptions in published summaries. It should be noted that all works dedicated to Samogitian bishops contain undeniable theatrical elements. This was brought about by the circumstances of the performance of works of this type: the bishops were congratulated publicly and thus it was not only the verbal rendition of a work that was important. For those who did not understand Latin or whose knowledge of this language was insufficient, the emblems put up in the hall of congratulation reflecting the main ideas of a work assisted in understanding the work. Annual letters (annuae litterae) that Jesuits used to send to Rome, historical outlines (historiae), and short catalogues of college residents (catalogi breves) from Kražiai are important sources of literary history. They contain unique information about the performance of some works and the works that have not reached us. Short catalogues of the Jesuits employed at the college during each academic year makes it possible to determine accurately the names of the professors that had taught rhetorics and poetic in a particular year. It was the teachers of these disciplines that mostly authored the panegyrics or were the main editors of these works. Analysis of the data showed that some authors who are well known today and who worked in Kražiai at that time (for example, Ioannes Chądzynski, Casimirus Koialowicz) might have penned the works that were earlier thought to be anonymous. The artistic level of the works created in Kražiai varies. There can be no doubt that the most valuable are the works by the authors who later gained fame as acclaimed poets of their time (Ioannes Chądzynski, Casimirus Koialowicz, Andreas Mlodzianowski). Nonetheless, all extant works concisely described in this paper point to the mastery of the rules of poetics and rhetoric, both by the Jesuit and layman students of Kražiai College, and by their professors. They demonstrate a high artistic level, add details to the literary picture of the Grand Duchy of Lithuania, and are a part of the literary and cultural heritage of Lithuania.